Analisis implementasi penerapan sasaran keselamatan pasien oleh perawat terhadap mutu pelayanan kesehatan di ruang rawat inap RSUD Dr. Pirngadi Medan - alfiany sahry; Arifah Devi Fitriani; Beni Satria (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2022)
Patient safety in hospitals is a service system that provides patient care to be safer. Based on preliminary survey data conducted at the Regional General Hospital Dr. Pirngadi Medan, it is known that the ISKP data for 2018 and 2019 are still many indicators that have not yet been reached. The purpose of this study was to analyze the effect of implementing the implementation of safety targets on the Quality of Health Services in the Inpatient Room of RSUD DR. Pirngadi Medan in 2020. This research is an analytical survey with a cross sectional study design conducted at RSUD DR. Pirngadi Medan in January to February 2020. The population in this study were all nurses in RSUD DR. Pirngadi Medan as many as 180 nurses. Sampling was done by cluster random sampling so that the samples in the study were 64 nurses. Research data were analyzed using the Chi Square formula and logistic regression. Based on the results of the study note that there is an influence on the application of patient identification correctly on the quality of health services, there is an effect on the application of improving effective communication on the quality of health services, there is an influence on the application of improving the safety of drugs that need to be aware of the quality of health services, there is an effect on the application of increasing the risk of infection related to health services to the quality of health services, there is an effect of the application of increasing the reduction in the risk of falling patients to the quality of health services in the Inpatient Room of RSUD DR. Pirngadi Medan in 2020 and as for the variables that most influence the quality of health services in the Inpatient Room of RSUD DR. Pirngadi Medan 2020 is the application of increasing the risk of falling patients.Based on the results of these studies it is recommended to the hospital to be able to carry out prevention programs so that it does not happen again.